2020
DOI: 10.3390/rs12020215
|View full text |Cite
|
Sign up to set email alerts
|

Improving Unmanned Aerial Vehicle Remote Sensing-Based Rice Nitrogen Nutrition Index Prediction with Machine Learning

Abstract: Optimizing nitrogen (N) management in rice is crucial for China’s food security and sustainable agricultural development. Nondestructive crop growth monitoring based on remote sensing technologies can accurately assess crop N status, which may be used to guide the in-season site-specific N recommendations. The fixed-wing unmanned aerial vehicle (UAV)-based remote sensing is a low-cost, easy-to-operate technology for collecting spectral reflectance imagery, an important data source for precision N management. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
111
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(123 citation statements)
references
References 83 publications
8
111
0
4
Order By: Relevance
“…Through their study, it was demonstrated that data curation could be modeled by these algorithms from a few to a high number of samples and still achieve appropriate results. In comparison with the proposed approach, other machine learning frameworks also adopted similar sample sizes, like 324 leaf measurements that were used to model the water-stress response from lettuce [23], 189 hyperspectral observations that were used to model grapevine water status [63], and 266 observations that were used as training to predict nitrogen content in rice fields [64].…”
Section: Machine Learning Analysis and Hyperspectral Mappingmentioning
confidence: 99%
“…Through their study, it was demonstrated that data curation could be modeled by these algorithms from a few to a high number of samples and still achieve appropriate results. In comparison with the proposed approach, other machine learning frameworks also adopted similar sample sizes, like 324 leaf measurements that were used to model the water-stress response from lettuce [23], 189 hyperspectral observations that were used to model grapevine water status [63], and 266 observations that were used as training to predict nitrogen content in rice fields [64].…”
Section: Machine Learning Analysis and Hyperspectral Mappingmentioning
confidence: 99%
“…The algorithms have the potential to model several types of datasets using linear and parametric and nonlinear and nonparametric approaches [12,27,28], including multispectral images [29]. Different machine learning algorithms like random forests (RF), decision trees (DT), artificial neural network (ANN), support vector machines (SVM), among many others, have been adopted to attend various applications in agriculture remote sensing [5,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al compared different machine learning methods (such as random forest (RF), neural network, partial least-squares regression, and regression trees) for estimating N content in winter wheat leaf using UAV multispectral images, and found that the fast processing RF algorithm performed the best among the tested methods [16]. Zha et al evaluated five approaches (single VI, stepwise multiple linear regression, RF, support vector machine, and artificial neural networks) for estimating the rice plant N uptake and N nutrition index in Northeast China, and they concluded that RF machine-learning regression can significantly improve the estimation of rice N status through UAV RS [27]. However, these studies used algorithms to improve the estimation accuracy without considering the image itself.…”
Section: Introductionmentioning
confidence: 99%